Assessing the pyloric caeca and distal gut microbiota correlation with flesh color in Atlantic salmon ( Salmo salar L., 1758) - Nguyen, CDH; Amoroso, G; Ventura, T; Elizur, A (Microorganisms, 2020)
The Atlantic salmon ( Salmo salar L., 1758) is a temperate fish species native to the northern Atlantic Ocean. The distinctive pinkred flesh color (i.e., pigmentation) significantly affects the market price. Flesh paleness leads to customer dissatisfaction, a loss of competitiveness, a drop in product value and, consequently, severe economic losses. This work extends our knowledge on salmonid carotenoid dynamics to include the interaction between the gut microbiota and flesh color. A significant association between the flesh color and abundance of specific bacterial communities in the gut microbiota suggests that color may be affected either by seeding resilient beneficial bacteria or by inhibiting the negative effect of pathogenic bacteria. We sampled 96 fish, which covered all phenotypes of flesh color, including the average color and the evenness of color of different areas of the fillet, at both the distal intestine and the pyloric caeca of each individual, followed by 16S rRNA sequencing at the V3-V4 region. The microbiota profiles of these two gut regions were significantly different; however, there was a consistency in the microbiota, which correlated with the flesh color. Moreover, the pyloric caeca microbiota also showed high correlation with the evenness of the flesh color (beta diversity index, PERMANOVA, p = 0.002). The results from the pyloric caeca indicate that Carnobacterium , a group belonging to the lactic acid bacteria, is strongly related to the flesh color and the evenness of the color between the flesh areas.